Plasmon-Coupled Fluorescence Probes: Effect of Emission Wavelength on Fluorophore-Labeled Silver Particles - Zhang, Jian (2008)
We examined the emission intensity and wavelength of 40 nm diameter silver particles covalently coated with organic fluorophores with different absorption and emission wavelengths. The objective of this study is to use the interactions of fluorophores with the plasmon in the metal particles to create the brightest possible probes. We refer to the complexes as plasmon-coupled fluorescence probes (PCPs). The fluorophores were separated from the metal cores by 10 nm long polymer backbones. The fluorescence was observed to be enhanced for seven fluorophores with emission wavelength from 450 to 700 nm. The enhancement efficiency was shown to approximately increase with long wavelengths for the silver particle-bound fluorophores. When comparing a single fluorophore free in solution and bound to the silver particle, the emission intensity increases 3- to 17-fold. The relationship between the enhancement efficiency and loading number of fluorophore on each silver particle was studied to optimize the conditions for PCP brightness. Compared with the free single fluorophores in the absence of metal, the optimized single labeled silver particles were even more than 1000-fold brighter, showing their potentials in the applications of sensitive clinical and biological assays.